Rootstock Alleviates Salt Stress in Grafted Mulberry Seedlings: Physiological and PSII Function Responses - Zhang, Huihui; Li, Xin; Zhang, Shubo; Yin, Zepeng; Zhu, Wenxu; Li, Jinbo; Meng, Liang; Zhong, Haixui; Xu, Nan; Wu, Yining; Sun, Guang yu (Frontiers in Plant Science, 2018)
This study investigated the effect of NaCl stress on Na+ and K+ absorption and transport by roots, nitrogen and phosphorus content in leaves, PSII photochemical activity and reactive oxygen species (ROS) in leaves of mulberry own-root seedlings and grafted seedlings. To determine the response, own-root seedlings of a high yielding mulberry cultivar, Tieba mulberry (Morus alba L.), and the grafted seedlings, obtained by using Qinglong mulberry with high salt tolerance as rootstock and Tieba mulberry as scion, were used. The Na+ content in roots and leaves of grafted seedlings was significantly lower than that in own-root seedlings under salt stress; while K+ content in roots and leaves of grafted seedlings was significantly higher than that in own-root seedlings. The root activity in grafted seedlings was significantly higher than that in own-root seedlings, as well as the content of nitrogen, phosphorous and water. PSII photochemical activity in leaves of grafted seedlings was less significantly affected by salt stress compared to own-root seedlings. The electron transport at the acceptor side of PSII from QA to QB was less affected by salt stress, which resulted in a significantly lower ROS content in leaves of grafted seedlings than that of own-root seedlings. Therefore, grafting high-yielding and good-quality Tieba mulberry with salt tolerant Qinglong mulberry as rootstock showed a relatively high salt tolerance. This may be because (1) the root system of rootstock presented high Na+ resistance and has selective absorption capacity for Na+ and K+ (2) the root system of rootstock prevented excess Na+ from being transported to aerial parts in order to reduce adverse effects of Na+ (3) the root system of rootstock had enhanced root activity under salt stress, which accelerated water and nutrient absorption (4) the leaves of grafted seedlings had higher PSII photochemical activity and electron transport rate compared with those of own-root seedlings under salt stress, which effectively reduced ROS burst mediated by photosynthesis and reduced oxidative damage.